Bioethics, person and family : A Bioethics that humanizes - Vassallo Cruz, Kathya Lisseth (2019)
In recent decades, the influence of postures has been perceived, and reductionist currents have been evidenced that have emptied content to Bioethics and affected its exercise. It is through the requirement of the ontological assessment of the person that it becomes the necessary foundation for an adequate practice of Bioethics, in an imperative need to rescue and replenish the original ethical bases of the person from whom the Bioethical decision making that affects and results in the human being, the family, future generations and the environment